Analisis faktor-faktor yang mempengaruhi penerapan konservatisme dalam akuntansi (studi pada perusahaan manufaktur yang terdaftar di bursa efek indonesia periode 2009-2011) - Tri Novikasari; Kirmizi Ritonga; Azhari Sofyan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aimed to analyze the effect of consisted of managerial ownership structure, institutional ownership structure, the structure of public ownership, Leverage and Growth Opportunities on conservatism in accounting. This population is a manufacture company registered in Indonesian Stock Exchange in 2009-2011. There is 14 companies in the sample with purposive sampling technique.The Method of analysis used in this study is logistic regression with sofware SPSS (Statistical Product and Service Solution) support. The examine of data used in this study for multiple regression analysis.The results of this study showed that the institutional ownership structure (sig=0,020; sig≤0,05) and Growth Opportunities (sig=0,039; sig≤0,05) effects on the conservatism in accounting. While the for managerial ownership structure (sig=0,973; sig≥0,05), the structure of public ownership (sig=0,854; sig≥0,05), and Leverage (sig=0,791; sig≥0,05) had no effect on the conservatism in accounting.Keywords : Managerial ownership structure, Institutional ownership structure, The structure of public ownership, Leverage, Growth Opportunities and Conservatism